Fenomenologia e ontologia da consciência em Jean-Paul Sartre - Santos, Tiago Soares dos (2012)
The problem that motivated us in the preparation of this study was to answer the question: how does the appearance of the world and how to become aware of such an appearance? Problem that Sartre and became the maximum of existentialism where the existence precedes the essence. We`ll try, in the course of our work, presenting the arguments used by Sartre that justify such affirmation and check if, in fact, it is possible to agree with an existential philosophy along the sartrianos lines. For that, we`ll see the phenomenological method that will assist us in the reflection on the fundamental structures of mundane appearance, central theme present in the husserliana phenomenology and sartriana`s foundation. This appearance will reveal the human reality as emanating from the most intimate of be; this human reality will be described in phenomenological philosophy of Sartre as consciousness, which conceptualizes as intentionality. Being intentionality is to take the constant motion of transcendence, that is, the exit of yourself. So it is necessary to expel everything there is or inhabits the consciousness. Making empty consciousness or translucent, requires that we understand the consciousness. Being conscious is to exist and the question of existence arises immediately with the human reality that asks about your way of being in the world. We will approach the existential problems of consciousness and the need for recognition of the same existence from reflexivity. In this way, we will develop how consciousness exists immediately, this is, how the consciousness appears intended to the objects of the world, how if seizes, first as a way thoughtless as a phenomenon of world. This mundane phenomenon that reveals the consciousness and is, at the same time, revealed by it. In this way, the appearances of world and consciousness occur simultaneously and interdependent. This concurrency between world and consciousness are the poles of the same phenomenon. It is the monism of the phenomenon that is constituted of these two realities of being, that is, the object appeared – the In-himself and the consciousness - the To-himself - are constituent parts of the same reality that cannot be seized separately. The existence, although unique, is paradoxically, constituted of two modalities of being. Despite having to recognize these two modalities to be as amalgamated, we can only recognize them from a long journey argumentative of phenomenological reflection, once we can only recognize the existence of the world and consciousness from the phenomenological process of reflexivity. In other words, we can only know what already exists since the knowledge doesn´t have itself the creative force or the power to confer being what is not yet or does not exist. Thus, the knowledge or the reflection are fundamental to the development of phenomenology, although this same phenomenology requires the recognition of something prior or immediate that precedes it and enables your cognitive achievement.